2021
DOI: 10.1186/s13018-021-02310-y
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of patient-specific cutting guides with disposable instrumentation in total knee arthroplasty: a case control study

Abstract: Background Total knee arthroplasty (TKA) is most frequently planned using conventional two-dimensional weight-bearing lower limb radiographs and is performed with conventional femoral and tibial cutting guides. Questions have been raised about the accuracy of conventional TKA instrumentation and planning for an anatomically standard or complex joint. Use of computed tomography (CT)-based three-dimensional (3D) templating and patient-specific cutting guides printed in 3D has shown improved posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Despite the emergence of patient-specific instrumentation, standard cutting guides, navigation, and accelerometer-based navigation, these new operation approaches are costly [ [19] , [20] , [21] ]. Recently, the robotic-assisted TKA system has been introduced to clinical practice for TKA [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the emergence of patient-specific instrumentation, standard cutting guides, navigation, and accelerometer-based navigation, these new operation approaches are costly [ [19] , [20] , [21] ]. Recently, the robotic-assisted TKA system has been introduced to clinical practice for TKA [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the included studies three were randomised controlled trials[ 27 , 38 , 44 ], twenty-one were retrospective studies[ 11 , 12 , 28 - 31 , 33 , 34 , 36 , 37 , 40 - 43 , 46 , 49 - 52 , 56 ], seven were prospective studies[ 32 , 35 , 39 , 45 , 47 , 48 , 55 ] and one was a theoretical cohort study[ 54 ]. Publication years ranged from 1998 to 2020.…”
Section: Resultsmentioning
confidence: 99%
“…This was mainly caused by the presence of randomization bias. Thirteen non-randomised studies were assessed, of which eleven had a moderate risk of bias[ 11 , 31 , 36 , 41 , 42 , 48 , 49 , 51 , 52 , 55 , 56 ]. One single study showed a low risk of bias[ 40 ] and one study showed serious risk of bias[ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the PSI conserves a high interest for other reasons than the surgical accuracy. The PSI is recently used with customized implants [30], or to improve the cost-efficiency ratio in operating room with the concept of singleuse instrumentation [31,32]. Even if clear advantages and superiority of these assistive technologies are not yet proven, these innovations allow to progress slowly.…”
Section: Discussionmentioning
confidence: 99%